The Undescended Testis in Adult Life: A Case Report - Fabianus Ferdian Damario; Alicka Octorevia Witjaksono; Angela Mulyana Sugiaman; Kellen Clementine; Yeppy Arief Nurzaman (Rumah Sakit Unggul Karsa Medika, 2022)
Background Cryptorchidism or Undescended testis (UDT) is a common birth defect in male genitalia, in which at least one testicle is absent from the scrotum. The missing testicle can be found along the inguinal canal or in the ectopic case could go as far as the pre-pubic area or perineum. Case report A 35-year-old man came to the Unggul Karsa Medika Hospital with a complaint of a lump in the right groin. He said that his lump has been felt since the patient was a child, comes and goes, and has become more clearly visible in the last 2 weeks. On physical examination, a lump was found in the right inguinal area without discoloration and pain, with a negative Valsalva test, and no right testicle was found. Conclusion It is possible that abnormality in intrauterine hormonal function has a role in the etiology of UDT. Adult UDT usually happens due to late diagnosis by physician and lack of insight of the parents about surgery necessity and its complications. Reduced fertility, risk of cancer, testicular torsion, as well as psychological issues are factors that supports the need for surgery. Orchiectomy remains the treatment of choice for adult UDT, including in our case, due to the risk of testicular cancer.